2023
DOI: 10.3390/toxins15060390
|View full text |Cite
|
Sign up to set email alerts
|

The Clostridium botulinum C2 Toxin Subunit C2IIa Delivers Enzymes with Positively Charged N-Termini into the Cytosol of Target Cells

Abstract: The binary Clostridium (C.) botulinum C2 toxin consists of two non-linked proteins. The proteolytically activated binding/transport subunit C2IIa forms barrel-shaped homoheptamers, which bind to cell surface receptors, mediate endocytosis, and translocate the enzyme subunit C2I into the cytosol of target cells. Here, we investigate whether C2IIa can be harnessed as a transporter for proteins/enzymes fused to polycationic tags, as earlier demonstrated for the related anthrax toxin transport subunit PA63. To tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(130 reference statements)
0
0
0
Order By: Relevance
“…lethal (LF) or oedema factors (EF) for PA and C2‐I subunit in the case of C2‐II, to cause cellular toxicity (Schleberger et al., 2006 ; Sherer et al., 2007 ). In agreement with this, several studies have shown that both PA and C2‐II proteins are non‐toxic in the absence of their respective binary partners (Collier & Young, 2003 ; Friedlander, 1986 ; Heber et al., 2023 ). Moreover, both PA and C2‐II proteins possess a conserved phenylalanine residue at position 425, which is a critical functional amino acid of the φ‐clamp to catalyse the translocation of their corresponding enzymatic components (i.e.…”
Section: Assessmentsupporting
confidence: 54%
“…lethal (LF) or oedema factors (EF) for PA and C2‐I subunit in the case of C2‐II, to cause cellular toxicity (Schleberger et al., 2006 ; Sherer et al., 2007 ). In agreement with this, several studies have shown that both PA and C2‐II proteins are non‐toxic in the absence of their respective binary partners (Collier & Young, 2003 ; Friedlander, 1986 ; Heber et al., 2023 ). Moreover, both PA and C2‐II proteins possess a conserved phenylalanine residue at position 425, which is a critical functional amino acid of the φ‐clamp to catalyse the translocation of their corresponding enzymatic components (i.e.…”
Section: Assessmentsupporting
confidence: 54%
“…C2-I is an ADP ribosyltransferase that modifies actin leading to the breakdown of the actin cytoskeleton and cell rounding. Comparable to anthrax toxin, the N-terminal part of C2-I or a polycationic tag sufficiently mediates the binding and transport of cargo proteins through the C2-II pore [29]. Using this method, the C2 toxin also has been engineered to deliver proteins into mammalian cells [30].…”
Section: Toxins Forming Pores For Delivery Of An Enzymementioning
confidence: 99%